Peran Media Massa Mengawal Pemilihan Umum Kepala Daerah - Sakir, Icuk Muhammad; Marleni, Marleni (Jurnal Publisitas, 2024)
This research aims to measure the role of mass media in overseeing the Regional Head Election of Palembang City in 2024. The research method used is quantitative descriptive. Quantitative data was collected using a questionnaire distribution technique, field observations were then presented in tabular form, then analyzed based on the results of data tabulation using . The data analysis technique used was SPSS ver.24 software. The research results show that conventional media (print, electronic and online) are able to raise the hopes of communicants, but they cannot yet determine their choices. The research data shows that the highest score of respondents' answers lies in the indicator. The message or invitation of regional head candidates arouses the needs and desires of the target audience to have a better life in the future. Mass media is only a communication tool that functions to motivate voters to participate in selecting regional head candidates who have a good track record, however, the characteristics of voters consisting of traditional, rational, critical voters and skeptical voters make it difficult for regional head candidates. determine the mass base. Conventional media must continue to disseminate balanced information about regional head candidates. This message packaging is really needed to raise the hopes of communicants so that they don't make mistakes in choosing leaders who can bring about change.